Polyphenol Extracts from Sage (Salvia lavandulifolia Vahl) By-Products as Natural Antioxidants for Pasteurised Chilled Yoghurt Sauce - Cristina Cedeño-Pinos; Antonia María Jiménez-Monreal; María Quílez; Sancho Bañón (MDPI AG, 2023)
Sage by-product extracts (SE) are a valuable source of phenolic acids and flavonoids for food applications. The objective was to test two SE as antioxidants in pasteurised chilled yoghurt sauces against oxidation. Two SE of different polyphenol total content and profile were selected: SE38 (37.6 mg/g) and SE70 (69.8 mg/g), with salvianic and rosmarinic acid as the main polyphenols, respectively. Four experimental low-fat yoghurt sauces were formulated: untreated; SE70/2 (0.16 g/kg); SE38 (0.3 g/kg); and SE70 (0.3 g/kg). The stability of phenolic acids, microbiological quality (mesophilic bacteria, moulds and yeasts, and L. monocytogenes), and oxidative stability (lipids, colour, and pH) were studied in the sauces after pasteurisation at 70 °C for 30 min (day 0) and stored by refrigeration (day 42). Pasteurisation and further chilling ensured the microbiological quality and inhibition of microbial growth could not be evidenced, although SE70 showed some antimicrobial potential. Both SE showed good properties as antioxidants for yoghurt sauces. This finding was based on two results: (i) their main polyphenols, salvianic and rosmarinic acids, resisted to mild pasteurisation and remained quite stable during shelf life; and (ii) SE improved radical scavenging capacity, delayed primary and secondary lipid oxidation, and increased colour stability, contributing to sauce stabilisation. SE38 had a better antioxidant profile than SE70; therefore, the selection criteria for SE should be based on both quantity and type of polyphenols. Due to their stability and antioxidant properties, sage polyphenols can be used as natural antioxidants for clean-label yoghurt sauces.